Peran Administrasi Keuangan dalam Mutu Pendidikan di SMK IT Arsitek Kota Bengkulu - Chandra Novianto; Hamdan Junaidi (Al-Khair Journal: Management Education, 2026)
Abstract: Financial administration plays a strategic role in determining the quality of education, particularly in vocational high schools. However, the reality remains concerning due to the apparent financial limitations in meeting educational quality needs. This study aims to map, describe, and analyze the role of financial administration in educational quality at the Integrated Islamic Vocational High School of Architect in Bengkulu City. Using descriptive qualitative methods, data sources include observation, interviews, and documentation. The results of the study indicate that financial administration plays a significant role in determining the quality of education. Quality schools are supported by the welfare of educators and education personnel, increased professionalism, sufficient operational budgets, ease of student learning activities and complete facilities, as well as effective and efficient financial management. Forms of financial administration such as BOS and SPP budget management, are carried out through planning and preparation of a one-year budget, and the learning process becomes effective, the school's goals and objectives can be achieved. Financial administration is carried out through the ARKAS application (School Financial Planning and Budget Application), so that financial administration becomes effective, transparent, and accountable. The form of educational quality can be seen from the input, process, output and outcome of education, so that the realization of educator professionalism, effective learning processes, and the availability of educational facilities. Thus, financial administration plays an important role in determining the quality of education. Therefore, it can be recommended to increase the role of financial administration through needs-based planning, more effective and efficient management of budget resources, and comprehensive reporting in improving the quality of education in a sustainable manner.Keywords: The role of financial administration, quality of education, SMK IT Arsitek Kota Bengkulu. Abstrak: Administrasi keuangan memegang peran strategis dalam menentukan mutu pendidikan, terutama di sekolah menengah kejuruan. Namun, faktanya masih memprihatinkan karena terlihat keterbatasan keuangan dalam pemenuhan kebutuhan mutu pendidikan. Penelitian ini bertujuan untuk memetakan, mendeskripsikan, dan menganalisis peran administrasi keuangan dalam mutu pendidikan di Sekolah Menengah Kejuruan Islam Terpadu Arsitek Kota Bengkulu. Menggunakan metode kualitatif deskriptif, sumber data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa administrasi keuangan berperan penting dalam menentukan mutu pendidikan. Sekolah yang bermutu didukung kesejahteraan pendidik dan tenaga kependidikan, peningkatan profesionalisme, anggaran operasional yang cukup, kemudahan kegiatan belajar siswa dan fasilitas lengkap, serta pengelolaan keuangan yang efektif dan efisien. Bentuk administrasi keuangan seperti pengelolaan anggaran BOS dan SPP., dilakukan melalui perencanaan, dan penyusunan anggaran satu tahun, serta proses pembelajaran menjadi efektif, tujuan dan sasaran sekolah dapat dicapai. Administrasi keuangan dilakukan melalui aplikasi ARKAS (Aplikasi Rencana Keuangan dan Anggaran Sekolah), sehingga administrasi keuangan menjadi efektif, transparan, dan akuntabel. Bentuk mutu pendidikan dapat terlihat dari input, proses, output dan outcome pendidikan, sehingga terwujudnya profesionalisme pendidik, proses pembelajaran efektif, dan fasilitas pendidikan tersedia. Dengan demikian, administrasi keuangan berperan penting dalam menentukan mutu pendidikan. Oleh karena itu, dapat disarankan tingkatkan peran administrasi keuangan melalui perencanaan berbasis kebutuhan, pengelolaan sumber anggaran yang lebih efektif efisien, dan pelaporan yang komprehensif dalam meningkatkan mutu pendidikan secara berkelanjutan.Kata kunci: Peran administrasi keuangan, mutu pendidikan, SMK IT Arsitek Kota Bengkulu.